Azathioprine monotherapy in autoimmune blistering diseases: A feasible option for mild to moderate cases. Issue 3 (18th December 2017) - Kakuta, Risa; Yamagami, Jun; Funakoshi, Takeru; Takahashi, Hayato; Ohyama, Manabu; Amagai, Masayuki
Abstract: Azathioprine (AZP) is used as a corticosteroid (CS)‐sparing medication to treat autoimmune blistering diseases. In this study, we examined the efficacy of AZP and the feasibility of using AZP monotherapy (without CS) to treat pemphigus and pemphigoid. We performed a retrospective study of 10 Japanese patients (seven with pemphigus and three with pemphigoid) with mild to moderate disease activity who had been treated using AZP. The treatment efficacy was evaluated based on decreases in the disease activity scores and autoantibody titers. The results demonstrate that seven out of 10 cases (70%) were treated successfully using AZP monotherapy with no severe adverse effects. The disease activity scores of the successfully‐treated patients decreased to zero after 1–37.5 months (average, 11.9) and the average disease activity scores in these cases decreased significantly at 2 months (38.2 ± 36.6%) compared with the scores of the three patients who required additional systemic CS therapy (77.5 ± 3.5%) ( P < 0.05). Additionally, the autoantibody titers of five cases treated successfully using AZP decreased by half at 6 months. In conclusion, our findings suggest that AZP monotherapy is a viable treatment option for mild to moderate pemphigus and pemphigoid.